The effects of piece size and storage temperatures on minimally processed 'aurora-1' peaches - Martins, R. N. [UNESP]; Mattiuz, B. H. [UNESP]; Santos, L. O. [UNESP]; Donadon, J. R. [UNESP]; Mattiuz, C. F.M. (International Society for Horticultural Science (ISHS), 2012)
The production of minimally processed fruit has increased significantly in the last few years due to the high nutritional value, convenience and safety of minimally processed fruit. The objective of the present study was to evaluate the effects of the conservation temperature and processing conditions on the quality and shelf-life of minimally processed peaches. The processing procedure consisted of washing, sanitization, peeling and stone removal. To remove the stone, the fruit was cut longitudinally, and three types of products were obtained, including halves, quarters and one-eighth segments. The fruit pieces were immersed in 2% ascorbic acid for 3 min and were packed in rigid polystyrene trays (Meiwa© M-54) coated with 14 μm PVC film (OmnifilmTM) (about 200 g per pack). The pieces were stored at 65% RH at 3, 6 or 9°C for 12 days, and were evaluated every four days. The appearance, fresh mass loss, color, O2 and CO2 concentration, acidity, total soluble solids, total and soluble pectin content and ascorbic acid concentration were measured. Minimally processed peaches stored at 3°C maintained higher quality due to control of ripening and senescence Moreover, an interaction effect between one-eighth segments and a temperature of 3°C was observed, and fruit with a superior appearance and higher soluble solids content was obtained.
Keywords: Fresh-cut; Postharvest; Prunus sp.; Shelf-life